Calculation of fracture mechanic parameters via FEM for some cracked plates under different loads - Nhu, Ngo Huong; Giang, Nguyen Truong (Vietnam Journal of Mechanics, 2006)
This paper describes some results in analyzing cracked plates via FEM based on the procedures in CASTEM 2000 [1]. The basic methods for computing the crack parameters by the finite element analysis are presented. Some programs written by GIBIAN languages to solve problems for cracked plates are given. In possible cases, the numerical results are composed with analytical solution or testing result that gives a good agreement. The influence of plate configurations, the crack length, the external load type on the crack characteristic values are considered. The numerical analysis for inclined crack at angle and in arbitrary position of plate, the crack at hole in the plate, the crack of gravity dams are realized. The given results and programs can be applied to practical problems for controlling the brittle failure state of a structure